2012
DOI: 10.1074/jbc.m112.418012
|View full text |Cite
|
Sign up to set email alerts
|

A Lectin from the Mussel Mytilus galloprovincialis Has a Highly Novel Primary Structure and Induces Glycan-mediated Cytotoxicity of Globotriaosylceramide-expressing Lymphoma Cells

Abstract: Background: Studies on the diversity of carbohydrate-binding proteins (lectins) are important in glycobiology. Results: A lectin having a novel primary structure was isolated from a mussel and found to have a globotriose-dependent cytotoxicity on Burkitt lymphoma cells. Conclusion: A new primary structure quite distinct from known lectin is described. Significance: Discovery of similar lectin structures from vertebrates will lead to progress in medical sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 58 publications
2
68
0
1
Order By: Relevance
“…Overall, about 20 different genes encoding proteins with a ricin domain are present in the C. gigas genome: most of them pertain to the well-known class of a-N-acetylgalactosaminyltransferases, enzymes which are involved in the biosynthesis of Mucin-type O-glycans. A novel lectin named MytiLec, with globotriose-dependent cytotoxicity, has been recently identified in M. galloprovincialis [65], and later a very similar lectin with antibacterial activity was identified in Crenomytilus grayanus [66]. These lectins share a structural motif with three very similar tandem repeats of about 50 amino acids, recognizable as a ricin-type beta trefoil domain.…”
Section: Extracellular Prrsmentioning
confidence: 98%
“…Overall, about 20 different genes encoding proteins with a ricin domain are present in the C. gigas genome: most of them pertain to the well-known class of a-N-acetylgalactosaminyltransferases, enzymes which are involved in the biosynthesis of Mucin-type O-glycans. A novel lectin named MytiLec, with globotriose-dependent cytotoxicity, has been recently identified in M. galloprovincialis [65], and later a very similar lectin with antibacterial activity was identified in Crenomytilus grayanus [66]. These lectins share a structural motif with three very similar tandem repeats of about 50 amino acids, recognizable as a ricin-type beta trefoil domain.…”
Section: Extracellular Prrsmentioning
confidence: 98%
“…New Gal-specific lectin MytiLec (later renamed to MytiLec-1 [14], the new name was used in present review) with globotriose-dependent cytotoxicity was recently identified in the mussel Mytilus galloprovincialis [12], and later it was reported about lectin CGL from the mussel Crenomytilus grayanus with similar amino acid sequence and antibacterial activity [15]. Analysis of the protein sequences of these lectins ( Figure 1) showed that they form a novel lectin family, sharing common structure-three tandem repeats with similar sequences to each other consisting of 40 amino acids and three carbohydrate-binding sites in each sub-domain.…”
Section: Novel Lectin Family Structurementioning
confidence: 99%
“…Today a large number of galactosyl-binding lectins have been reported to occur in the invertebrates, which bind to D-galactose, its derivatives, and D-galactose containing complex carbohydrates in a very selective manner [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, lectins have been developed to form useful agents to analyze glycofiles and biomarkers for a variety of cancers, including pancreatic cancer [1], aggressive breast cancer [2,3], ovarian cancer [4], prostate cancer [5], and liver cancer [6], as well as cytotoxic agents for inducing cancer cells apoptosis or autophagy [7][8][9][10]. Previously, we determined that, through adenovirus-mediated gene delivery, lectins including mannose binding plant lectin Pinellia pedatisecta agglutinin (PPA) as well as marine lectins such as galectin Anguilla japonica lectin 1 (AJL1), Haliotis discus discus sialic acid binding lectin (HddSBL), Dicentrarchus labrax fucose binding lectin (DlFBL), and Strongylocentrotus purpuratus rhamnose binding lectin (SpRBL) elicited cytotoxicity to a variety of cancer cells [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%